PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. AMANAH FINANCE - faradilla Aslia A (Jurnal Ilmu Manajemen Profitability, 2019)
The purpose of this study was to determine and analyze the influence of the work environment on employee performance at PT. Amanah Finance Makassar City. The type of research used in this research is quantitative descriptive. The results of the regression analysis show that the two variables included in the model namely the variable X (work environment) and Y (employee performance) have a positive and significant influence. This is indicated by the F-count value of 77,209 greater than the F-table of 3,48 (F-hit 77,209 F-table 3,48). Correlation coefficient value (r) of 0.717 indicates that the degree of closeness of the relationship between work environment variables and work motivation is very strong because the r value is very close to 1. Furthermore, the level of determination (r2) is 0.514, indicating the model predictive power of 51.4%. This means that 58% of the variation in the rise and fall of work motivation is influenced by the ups and downs of the work environment while the remaining 49% is influenced by other factors not included in the analysis model.Keywords: Work Ability Against Employee Performance